Ibrahim Yazdi: His Life and Political Activities in Iran until 1979 - Khalaf, Ass.Prof Haider Ali (Thi Qar Arts Journal, 2023)
Ibrahim Yazdi is considered one of the most mysterious revolutionary figures in Iran, as he worked with the movements opposing the Shah’s regime early in his life. His political activity emerged since 1946 when he joined the "Servants of God Socialist" movement, and then became a prominent member of the National Front after the fall of the government. Dr. Muhammad Mossadeq in 1953, after which he emigrated to the United States of America in 1961 and led the opposition movement abroad until 1979, the year in which he returned to the country after a trip of absence that culminated in political activity opposing the Shah’s regime. His name was associated with Mr. Khomeini in France and he returned with him to Iran, and although he assumed the position of Minister of Foreign Affairs of the country in the interim government formed by Mehdi Bazarkan, he soon resigned from it following the attack on the American Embassy on November 4, 1979 and its repercussions on Iran and its international isolation. The strongest opponent of the policy of what was known at the time as the "revolutionary government", because he believed that it contradicted the principles of human rights and international treaties.